How I Became a Non-Chemist - Menningen, Ken (My University, 2018)
Some scientists direct their careers with laser focus to answer a small set of questions. Others wander around like a trapped photon. I will tell the story about how a plasma physicist ended up studying combustion chemistry, and how the student he trained learned about growing diamonds, thermophoresis, synchrotrons, radiation trapping, photoelectrochemical water splitting, and anticrepuscular rays.